Iridium(iii) bis(thiophosphinite) pincer complexes: synthesis, ligand activation and applications in catalysis. Issue 26 (24th June 2022) - Linke, Alexander; Decker, David; Drexler, Hans-Joachim; Beweries, Torsten
Abstract : Iridium(iii ) bis(thiophosphinite) complexes of the type [( R PSCSP R )Ir(H)(Cl)(py)] ( R PSCSP R = κ 3 -(2, 6-SPR2 )C6 H3 ) (R = t Bu, iPr, Ph) can be prepared from the ligand precursors 1, 3-(SPR2 )C6 H4 by C–H activation at Ir [Ir(COE)2 Cl]2 or [Ir(COD)Cl]2 . Abstract : Iridium(iii ) bis(thiophosphinite) complexes of the type [( R PSCSP R )Ir(H)(Cl)(py)] ( R PSCSP R = κ 3 -(2, 6-SPR2 )C6 H3 ) (R = t Bu, iPr, Ph) can be prepared from the ligand precursors 1, 3-(SPR2 )C6 H4 by C–H activation at Ir using [Ir(COE)2 Cl]2 or [Ir(COD)Cl]2 . Optimisation of the protocol for complexation showed that direct cyclometallation in the absence or presence of pyridine, as well as C–H activation in the presence of H2 are viable options that, depending on the phosphine substituent furnish the five-coordinate Ir(iii ) hydride chloride complexes 2-R or the base stabilised species 3-R in good yields. In case of the Ph PSCSP Ph ligand, P–S activation results in the formation of a thiophosphine stabilised Ir(iii ) hydride complex [( Ph PSCSP Ph )Ir(H)(Cl)(PPh2 SH)] (4 ). Reaction of 2- t Bu with H2 in the presence of base furnishes an Ir(iii ) dihydride complex (5 ) via a labile Ir(iii ) dihydride–dihydrogen complex (6 ). All complexes are inactive for transfer dehydrogenation of cyclooctane in the presence of NaO t Bu and tert -butylethylene, likely due to decomposition of the Ir complex in the presence of base at higher temperature.